Comparing the Effectiveness of Spiritual Therapy and Religious Coping Strategies Training on Anxiety and Depression in Women with Breast Cancer - Mona Mobayyeni; Neda Fatahi; Seyedeh Mansoureh Zekri; Ebrahim Abdoli; Mahbubeh pourjafari (Patient Safety and Quality Improvement Journal, 2025)
Introduction:Cancer disease and issues related to its treatment have been introduced as the most important stressors in breast cancer patients, which can cause psychological disorders in these patients. The purpose of this research was to compare the effectiveness of spiritual therapy and teaching religious coping strategies to reduce symptoms of anxiety and depression in women with breast cancer.  Materials and Methods: The current research was semi-experimental based on pre-test-post-test and follow-up (3 months later) design with control group. The statistical population comprised women diagnosed with breast cancer who attended Khatam Al-Anbia Cancer Hospital in Tehran from July to October 2023. A total of 45 patients were selected from this population using purposive sampling. The participants in the spiritual therapy experimental group participated in eight sessions of one 60-minute session per week, and the participants in the religious confrontation training group participated in ten sessions of one 60-90-minute session per week. Research tools included Beck Depression Inventory (BDI-II) and Zang Anxiety Inventory (SAS). The obtained data were statistically analyzed using covariance analysis with repeated measurements in SPSS version 27 software.Results: The results of this study indicated that there was no significant difference in depression scores between the spiritual therapy and religious coping groups (p = 1.000). However, both the spiritual therapy and religious coping groups showed significant improvements in depression compared to the control group (p < 0.01). Additionally, there was a significant difference in anxiety scores between the religious coping and spiritual therapy groups during the follow-up phase, as well as between these groups and the control group at follow-up (p < 0.001). Conversely, no significant difference was observed in anxiety levels between the spiritual therapy and religious coping groups (p > 0.05).Conclusion:The results of this study indicated the effectiveness of spiritual therapy and religious coping strategies in reducing anxiety and depression symptoms in women with breast cancer. By improving effective coping mechanisms in people, spirituality-based interventions can help patients to face and deal with anxiety and depression caused by the disease and its consequences in a positive and effective way.